Class 1 Integrons Increase Trimethoprim-Sulfamethoxazole MICs against Epidemiologically Unrelated Stenotrophomonas maltophilia Isolates - Barbolla, Raquel (American Society for Microbiology, 2004)
Twenty-five plasmid-specified antimicrobial resistance determinants common to gram-negative bacilli from nosocomial infection were investigated from 31 Stenotrophomonas maltophilia isolates. Twenty-four clones were identified by pulsed-field gel electrophoresis, and in three clones that exhibited an increased trimethoprim-sulfamethoxazole MIC, the sul1 determinant was found. These results support not only the higher spread of class 1 integrons compared to other mechanisms but also the potential limitation of using trimethoprim-sulfamethoxazole for therapy of severe S. maltophilia infections.